Maize and Prairie Root Contributions to Soil CO2 Emissions in the Field. Issue 5 (1st September 2016) - Nichols, Virginia; Miguez, Fernando; Sauer, Thomas; Dietzel, Ranae
Abstract : Increasing soil carbon content via agricultural practices not only enhances the production potential of the land, but also counteracts rising atmospheric CO2 levels. When predicting production systems' effects on soil carbon, quantifying CO2 efflux derived from live roots is of particular importance as it is a through‐flux and does not signify depletion of soil carbon. This field study aimed to measure and compare soil CO2 emissions derived from roots in annual and perennial agroecosystems. We used periodic 48‐hour shading over two growing seasons to estimate root growth‐derived CO2 in continuously grown maize (CC) with grain and 50% stover harvested each year, unfertilized reconstructed tallgrass prairie (P), and the same prairie grown with spring nitrogen fertilization (PF), both which had biomass harvested post‐frost. In CC, P, and PF root‐derived CO2 contributed to 28, 31, and 30% of each crop's respective growing season cumulative CO2 emissions in 2012, and 19, 24, and 28% in 2013, respectively. Season‐cumulative root‐derived CO2 was not proportional to end‐of‐season belowground biomass (BGB): P had nearly twice the BGB of PF, but their cumulative root‐derived fluxes were not significantly different in either year. A significant proportion of soil CO2 emissions is derived from roots, making it a critical process to consider when comparing or modeling soil emissions of cropped or prairie soils. Using BGB alone may not be a useful proxy for estimating root contributions.